Electronic payments as a way to reduce Transaction costs - Ruzmetov K.I (Zien Journals, 2023)
in this paper, we consider the possibility of using electronic payments, their advantages compared to bank payments, as well as the reduction of transaction costs of the market mechanism and transaction costs of payments.
Keywords: transaction costs; electronic payments; online transfer; bank